2021
DOI: 10.47197/retos.v43i0.88903
|View full text |Cite
|
Sign up to set email alerts
|

Learn-to-swim program in a school context for a twelve-week period enhance aquatic skills and motor coordination in Brazilian children (Las clases de natación en el contexto escolar durante un período de doce semanas mejoran las habilidades acuáticas y l

Abstract: This study aimed to verify the effects of 12 weeks of swimming lessons implemented in age school Brazilian children’s aquatic skills and motor coordination. Fifty children aged 6 to 10 years old (mean ± SD: 8.34 ± 1.10 years), participated in one swimming lesson per week provided by the school curriculum. Each child was evaluated for their aquatic skills (17 skills checklist) and motor coordination (Körperkoordinationstest Für Kinder test–KTK) before and after the swimming program. This study showed sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 27 publications
2
20
0
3
Order By: Relevance
“…Additionally, Pîrjol et al [ 47 ] found significant improvements in some scores of motor skill development (EUROFIT tests 2 ( p = 0.002) and 4 ( p = 0.001)) and Moura et al [ 8 ] found significant improvements in both basic and formal swimming skill interventions pre–post testing; the KTK test highlighted significant improvements in motor coordination (basic and formal p < 0.01). Moura et al’s [ 9 ] second study also found significant results of improved motor coordination ( p < 0.01) and improved aquatic skills ( p < 0.01), as a result of the swimming intervention.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…Additionally, Pîrjol et al [ 47 ] found significant improvements in some scores of motor skill development (EUROFIT tests 2 ( p = 0.002) and 4 ( p = 0.001)) and Moura et al [ 8 ] found significant improvements in both basic and formal swimming skill interventions pre–post testing; the KTK test highlighted significant improvements in motor coordination (basic and formal p < 0.01). Moura et al’s [ 9 ] second study also found significant results of improved motor coordination ( p < 0.01) and improved aquatic skills ( p < 0.01), as a result of the swimming intervention.…”
Section: Resultsmentioning
confidence: 94%
“…Of the final 10 studies, only 2 originated in the UK [ 7 , 10 ]. The remaining eight originated from various countries, including Portugal [ 8 , 9 , 48 ], Serbia [ 6 , 45 ], Romania [ 47 ], Poland [ 46 ], and Turkey [ 5 ]. All studies reported gender and age as required by the inclusion/exclusion criteria; participants of the studies were predominantly male: out of a combined total of 611 participants from all studies, 429 (70.2%) were male, and only 182 (29.8%) were female.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…El ser humano es un individuo social, activo y consciente inmerso en un entorno cambiante, donde constantemente se encuentra interactuando con el medio ambiente que lo rodea (Gallahue & Ozmun, 2005;Granda & Alemany, 2001;Trigo, 2000). Por esta razón, el sujeto a través del movimiento y sus destrezas motrices (Jiménez & Araya, 2012) establece unas dinámicas deportivo-sociales que le permiten responder a las diferentes situaciones del contexto (Logan, Robinson, Wilson & Lucas, 2011;Becerra-Patiño, Ortiz-Quezada, Chaves-Cárdenas, Pachon-Cañas & Ramírez-Alvarado, 2022;Moura et al, 2022). Allí, el dinamismo y eficiencia con el que ejecute dichas acciones dependerá de que tan activo y consciente sea ese movimiento como proyección de su cuerpo (Backes, Porta & Difabio De Anglat, 2015).…”
Section: Introductionunclassified